Egypt: Land of a Glorious And Enviable Past (Some Reflections) - Gabriel, Selvamany (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The following is an illustration of Egypt’s greatness under the rule of the mighty Pharaohs. The Great Pharaohs of this era included Amenhotep I, Thutmose 1, Thutmose II, Queen Hatsheput, Thutmose III and Amenhotep II, spanning a time period of between 1546 B.C. to 1425 B.C. Egypt, by all accounts, was a sophisticated land and its culture was regarded as advanced for its time. The Egyptian language of hieroglyphics was no simple medium of communication. Hieroglyphics is by far the most difficult language ever put into writing. It uses pictographs and not characters. Present day scholars are of the opinion that the study of this language involves a lifetime of mastery even for the brilliant. The nation had the best universities of their time, not to mention an enviable economic situation.